Trends in aortic dissection hospitalizations, interventions, and outcomes among medicare beneficiaries in the United States, 2000-2011 - Mody, Purav S; Wang, Yun; Geirsson, Arnar; Kim, Nancy; Desai, Mayur M; Gupta, Aakriti; Dodson, John A; Krumholz, Harlan M (Circulation Cardiovascular quality and outcomes, 2014)
The epidemiology of aortic dissection (AD) has not been well described among older persons in the United States. It is not known whether advancements in AD care over the last decade have been accompanied by changes in outcomes. The Inpatient Medicare data from 2000 to 2011 were used to determine trends in hospitalization rates for AD. Mortality rates were ascertained through corresponding vital status files. A total of 32 057 initial AD hospitalizations were identified. The overall hospitalization rate for AD remained unchanged at 10 per 100 000 person-years. For 30-day and 1-year mortality associated with AD, the observed rate decreased from 31.8% to 25.4% (difference, 6.4%; 95% confidence interval [CI], 6.2-6.5; adjusted, 6.4%; 95% CI, 5.7-6.9) and from 42.6% to 37.4% (difference, 5.2%; 95% CI, 5.1-5.2; adjusted, 6.2%; 95% CI, 5.3-6.7), respectively. For patients undergoing surgical repair for type A dissections, the observed 30-day mortality decreased from 30.7% to 21.4% (difference, 9.3%; 95% CI, 8.3-10.2; adjusted, 7.3%; 95% CI, 5.8-7.8) and the observed 1-year mortality decreased from 39.9% to 31.6% (difference, 8.3%; 95% CI, 7.5-9.1%; adjusted, 8.2%; 95% CI, 6.7-9.1). The 30-day mortality decreased from 24.9% to 21% (difference, 3.9%; 95% CI, 3.5-4.2; adjusted, 2.9%; 95% CI, 0.7-4.4) and 1-year decreased from 36.4% to 32.5% (difference, 3.9%; 95% CI, 3.3-4.3; adjusted, 3.9%; 95% CI, 2.5-6.3) for surgical repair of type B dissection. Although AD hospitalization rates remained stable, improvement in mortality was noted, particularly in patients undergoing surgical repair.